Quantitative analysis of water quality and heavy metals in water, sediments and tissues of Grey Mullet (Mugil cephalus) from the Negombo estuary - Mendis, B.R.C.; Najim, M.M.M.; Kithsiri, H.M.P (Colombo Journal of Multi-Disciplinary Research, 2015)
The objectives of this study were to assess the levels of water quality and heavy metals of the water, sediments and fish tissues in the Negombo estuaries. For this study, samples were collected from sixteen sampling locations during the one year study period from January to December 2014. The results revealed that the average concentrations of ammonia, nitrate, pH, electrical conductivity, total suspended solids of 0.215±0.4mg/l, 1.08±0.98mg/l, 7.8±0.28, 29.6±1.56ms/cm, 29.2±0.35mg/l, levels were below the maximum permissible limits. Biochemical Oxygen Demand 24.8±1.3mg/l and Chemical Oxygen Demand 469.0±36.5mg/l levels were much higher than the permissible threshold limits of industrial wastewater quality standards for CEA,(2001) Sri Lanka. The results indicated that the concentrations (ppm) of heavy metals in water were Pb,0.01±0.0003; Cd,0.015±0.003; Hg,0.013±0.001; Zn,0.695±0.06; Cu,0.03±0.02; Cr,0.055±0.004 and Fe,0.485±0.04 respectively. The sediments concentrations (mg/kg) were Pb,7.95±0.95; Cd,1.06±0.23; Hg,0.001±0.52; Cu,0.042±3.2; Cr,14.30±1.5, Zn,154.25±3.2 and Fe,78.6±101.2 respectively. The concentrations (mg/kg) of metals in the fish tissues were Pb,0.57±0.48; Cd,1.045±0.28; Hg,0.05±0.046; Zn,119.2±111.3; Cu,4.60±1.64; Cr,5.22±2.49 and Fe,32.8±59.3 respectively. The highest concentrations of pollution status were recorded in the Northern region of the estuary.
Keywords: Fish Tissue, Heavy Metals, Pollution Status, Sediment, Water Quality